A Rare Presentation of Carcinoma Endometrium - Myat, San Yi; Soe, Lwin; Thidar, Soe; Khin, Than Yee (Universiti Malaysia Sabah, 2016)
Background Normally endometrial carcinoma presents with post-menopausal bleeding in the majority of cases. It rarely presents with haematometra. If it does, it rarely reaches the term pregnant uterus size. Case presentation This case report is a rare presentation of endometrial carcinoma which was at first diagnosed as a huge ovarian mass later found out to be haematometra intraoperatively. There was a discordant finding between the endometrial invasions with distant metastasis (Local invasion of stage 1A with lung metastasis which should be stage 4B). Conclusion It is an uncommon combined occurrence but at least we learnt there can be possible different presentation for endometrial cancer. It further proved that almost all of haematometra can turn out to be associated with endometrial carcinoma.